Bridging the gap: Aligning culture between ship and shore - May, Philippa (My University, 2023)
This thesis aims to find strategies for, and barriers to, cultural alignment between ship and shore. The results of this research show that: (1) to align culture between ship and shore, an organization must adopt a culture based on people‐first values, holistic communication, low powerdistance, and two‐way trust; and (2) the main barrier to ship‐shore alignment is a culture that contains elements of hierarchy, patriarchy, autocracy, and disjointed communication. The cultural elements that were shown to support alignment were also shown to negate the barriers. These barriers were found in a literature review to be common descriptors of ‘how it is to work at sea’. Together these points exhibit the crux of the issue: that seafaring culture itself prevents alignment between ship and shore. In other words, cultural alignment cannot be achieved if seafaring culture is allowed to remain in its current state. The results therefore highlight its tremendously problematic nature. The need for a different style of leadership is growing in the maritime industry as the cultural gap persists between ship and shore. A transformational type of leadership based on trust, holistic communication and people‐first values will serve to both negate the problematic aspects of seafaring culture and align culture between ship and shore. This will make it possible for seafarers to work in a culture that benefits both them and maritime organizations, taking into account the modern world, its challenges of complexity and ever‐increasing requirements for intellectual diversity.
Keywords: maritime, seafaring, culture, ship, shore, organization, trust, communication, hierarchy, power‐distance